2008
DOI: 10.1148/radiol.2491071517
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo 3D High-Spatial-Resolution MR Imaging of Intraplaque Hemorrhage

Abstract: With its high spatial resolution, MR imaging of IPH permits detection of plaque hemorrhage location, resulting in strong agreement between imaging and histologic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 24 publications
3
76
1
Order By: Relevance
“…We used the 3D-T1W fat suppresssed spoiled gradient echo or the 2D-T1W inversion recovery turbo field echo MR imaging sequence to detect intraplaque hemorrhage. Bitar et al 25 and Cappendijk et al 26 used sequences like ours and found a good sensitivity, specificity, and interobserver agreement for the detection of intraplaque hemorrhage in both sequences. They also found good agreement between MR imagingdepicted intraplaque hemorrhage and histologic sections.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We used the 3D-T1W fat suppresssed spoiled gradient echo or the 2D-T1W inversion recovery turbo field echo MR imaging sequence to detect intraplaque hemorrhage. Bitar et al 25 and Cappendijk et al 26 used sequences like ours and found a good sensitivity, specificity, and interobserver agreement for the detection of intraplaque hemorrhage in both sequences. They also found good agreement between MR imagingdepicted intraplaque hemorrhage and histologic sections.…”
Section: Discussionmentioning
confidence: 54%
“…20 Based on the good sensitivity and specificity of MDCTA for plaque ulcerations and the good agreement between MR imaging-depicted intraplaque hemorrhage and histology, we therefore conclude that it is legitimate to use imaging techniques such as MDCTA and MR imaging to study the relationship between intraplaque hemorrhage and the disruption of the plaque surface. 25,26 Moreover, the use of MDCTA and MR imaging provides the opportunity to investigate the relationship in a specific category of patients-that is, those with a mild-to-moderate carotid artery stenosis, patients who are treated medically and thus have no available histology. The final limitation of our study is that it is cross-sectional.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the tissue thickness encompassed by imaging (mm) is different from the tissue thickness covered by immunohistochemistry (mm), and this difference is an inherent limitation of all such published studies (2)(3)(4)27). All published histologically validated carotid plaque studies have limitedsize populations, with heterogeneity in terms of symptoms, time to surgery, and medications (2)(3)(4)31), reflecting the logistic difficulties of these types of studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Magnetic resonance imaging (MRI) has emerged as a reliable and accurate tool for discriminating plaque components in vivo and for detecting IPH. 7,8 However, only few studies have investigated determinants of plaque composition in the carotid artery 9,10 and, specifically, studies relating risk factors to IPH are scarce. We recently reported that sex, age, smoking, and hypertension are associated with IPH in the general population.…”
mentioning
confidence: 99%